2022
DOI: 10.4331/wjbc.v13.i5.83
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin level in Sudanese women with unexplained infertility and its relationship with some reproductive hormones

Abstract: BACKGROUND The excessive concentration of leptin has negative effects on all aspects of female reproduction. Despite this established relationship, the exact role of leptin in women’s fertility is not clear enough and needs more clarification. AIM To evaluate the serum leptin levels in Sudanese women and to ascertain the relationship between serum leptin levels and unexplained infertility (UI). METHODS A matched (age and body mass index) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Elevated leptin levels have also been observed in various autoimmune diseases. 65,70 Abdullah et al 71 reported elevated leptin levels in women with unexplained infertility. High levels of leptin in serum and follicular fluid in women undergoing in vitro fertilization were negatively correlated with a non-receptive endometrium, rate of good quality embryos, and clinical pregnancy rate.…”
Section: Adipokinesmentioning
confidence: 99%
“…Elevated leptin levels have also been observed in various autoimmune diseases. 65,70 Abdullah et al 71 reported elevated leptin levels in women with unexplained infertility. High levels of leptin in serum and follicular fluid in women undergoing in vitro fertilization were negatively correlated with a non-receptive endometrium, rate of good quality embryos, and clinical pregnancy rate.…”
Section: Adipokinesmentioning
confidence: 99%